Movements of boreal caribou in the James Bay lowlands - Hazell, Megan E.; Taylor, Mark E. (Rangifer, 2011)
Little is known about the movements and home range of boreal woodland caribou (Rangifer tarandus) in the James Bay lowlands, northern Ontario. Our preliminary study involves the use of GPS collars with Argos satellite system uplink to monitor movements of caribou and 10 animals were collared in December 2004. Animals appeared to have reduced rates of daily movement starting approximately in mid to late December and stretching until late February. Similarly, most animals appeared to have very reduced rates of movement from the beginning of May to the end of June indicating that this is their calving period (includes both parturition as well as the period immediately after parturition). Thus the over-wintering range was assumed to be where the animals were from mid-December to late February and the calving range was defined as the area they were in from the beginning of May to the end of June. Individual home-ranges were typically large, the mean 90% kernel home range for 2004 - 2007 was 41 579 km2. Over wintering areas and calving areas were small when compared to annual home-range size and reflect the reduced rates of movement during these time periods. Female caribou show site fidelity to calving grounds, using the same core areas year after year. However, the same level of site fidelity was not observed in over-wintering areas. The caribou in the James Bay lowlands display behaviours that are characteristic of both the forest-tundra and forest-forest ecotypes which may warrant the reconsideration of the validity of proposed ecotypes with respect to protection under species-at-risk legislation.